ANALISIS KEMAMPUAN DAN KEMAUAN MEMBAYAR PASIEN RAWAT INAP DI RS PKU MUHAMMADIYAH BANTUL - Mudayana, Ahmad Ahid (Universitas Ahmad Dahlan, 2015)
AbstractBackground: The number of treatment options for making competition among hospitals increasingly stringent anyway though not the business competition. The amount of this option makes every hospital must calculate the unit cost of each so as to make the right policy in determining the hospital tariffs. PKU Muhammadiyah Bantul is one of the largest hospital in Bantul. The Muhammadiyah owned hospitals have a social mission in providing health services to the community. The social mission of making hospitals PKU Muhammadiyah Bantul in setting the rates must be in accordance with the ability of the community. This is because the target consumer PKU Muhammadiyah Bantul majority of the lower middle class people. Currently PKU Muhammadiyah Bantul is developing the building, including increasing the number of beds to 300. Increasing the number of beds will make PKU Muhammadiyah Bantul as the largest Muhammadiyah hospital in Yogyakarta. The existence of this development will be made possible due to changes in the level of rates increasing operational needs. Background of the researchers interested in studying the patients willingness and ability to pay in PKU Muhammadiyah Hospital in Bantul.Methods: This research is analytic research. Using cross sectional study design. The sample in this study amounted to 87 respondents.Results: Based on the analysis that has been carried out showed that the patient has the ability to pay an average of 100 033. While the average willingness to pay of patients included in the high category in the amount of 71.26 percent.Conclusions: 1) The average ability to pay inpatients Rp 100 033, estimated for three days. 2.) In order to conduct the promotion of hospital managers in an appropriate manner, for example by offering affordable rates to the public.Â Keywords: willingness to pay, ability to payÂ Â